Sustainable intensification of potato in rice based system for increased productivity and income of resource poor farmers in West Bengal, India - Arya, S.; Ahmed, M.; Bardhan Roy, S.K.; Kadian, M.S.; Quiróz, R. (2015)
The aim of present study was conducted was to increase productivity of exiting cropping systems and farmers income by expanding potato in non-traditional potato growing regions by adopting an innovative technology Double Transplanting (DT) of Rice and planting early maturing potato between two rice crops. This cropping pattern will enhance productivity of system without sacrificing area or productivity of either of the two crops. Similar work has been done earlier (Robin et al. 2007 and Burdhan Roy et al. 2007). The field trials were carried out at three locations Siliguri Subdivision of Darjeeling district to and Rajgunj block of Jalpaiguri district to introduce potato as sand witch crop between two rice crops. Eighty five farmers planted 18.6 acres land under rice-potato-rice system in 2013-14. Cost-benefit of different cropping systems was analyzed. Results revealed that “Potato-DT Rice” produced higher income/ha compared to traditional potato-boro rice and kharif (monsoon) rice-boro rice. The DT rice-potato system generated 27% higher income over traditional potato-boro rice and 290% over mono boro rice system. The gender responsive meetings, trainings and demonstrations were conducted. The farming community was motivated to adopt this new profitable cropping system in the region.